Minhāj al-ʿulā : Risalaʾī dar bāb-i ḥukūmat-i qānūn - Bihbihānī, Abū Ṭālib, (Miras Maktoob, ISBN: 9789004365452., 2019)
In the beginning, Qajar rulership (1210-1344/1796-1925) pretty much reflected the traditional, top-down leadership common among the Turkic tribes from which this dynasty had come forth. It was only under Nāṣir al-Dīn Shāh Qājār (r. 1264-1313/1848-96) that serious attempts at reforms were made, initially under Chancellor Mīrzā Taqī Khān, in office between 1264/1848 and 1268/1851. However, Amīr Kabīr's energetic initiatives met with internal resistence, leading to his downfall and subsequent murder in a bathhouse in Fin Garden, Kashan, in 1268/1852. In the years following, Nāṣir al-Dīn Shāh introduced various administrative initiatives, but ineffectiveness and internal resistence remained important impediments to genuine reforms. Well-structured and lucid, the present work by Abū Ṭālib Bihbihānī is one of several memoranda on reform that were sent to the shah in the course of his reign. Focussing on the separation of powers as codified in European constitutional law, many of its suggestions were implemented in Iran's first constitution of 1906-07.